Loss of epidermal glucocorticoid receptor protects against whole body metabolic dysfunction upon chronic corticosterone treatment - Andrea Gallego; Paloma Pérez (Elsevier, 2023)
Objective: Glucocorticoid (GC) excess contributes to the development of metabolic syndrome, defined by visceral obesity, abnormal glucose tolerance, and dyslipidemia. While it is accepted that loss of metabolic control is causative of cutaneous diseases, the systemic effects of epidermal dysfunction have received limited attention. Importantly, independent of GC blood levels, skin synthesis of these hormones can provide tissue-specific variations that may affect global homeostasis. We aimed to assess whether the epidermal-specific loss of the GC receptor (GR) had an impact on the dermal white adipose tissue (dWAT), a specialized fat depot functionally different from other fat pads, as well as on whole body homeostasis. Methods: GR epidermal KO (GREKO) and control female mice were treated with oral corticosterone (CORT) for 4 weeks, a protocol inducing metabolic dysfunction. Metabolic parameters including body weight, visceral and hepatic fat accumulation, blood glucose and insulin levels, glucose tolerance tests upon fasting, and triglycerides levels, were determined. Systemic alterations of soluble factors with known roles in immunity and inflammation were also assessed by a multiplex antibody array system containing selected cytokines, chemokines, and growth factors. The levels of cutaneous GCs and the profile of skin-secreted factors were determined in tissue explants by ELISA and the multiplex array system. Morphometric studies quantitated changes in dWAT thickness and adipocyte size in both genotypes, basally and at the end of CORT treatment. The expression of adipocyte markers was assessed in purified dermal adipocytes in vehicle and CORT-treated GREKO vs controls. Results: Despite similar circulating levels of GCs, GREKO mice were highly resistant to CORT-induced systemic metabolic anomalies including body weight gain, visceral and hepatic fat, hyperglycemia, insulinemia, and elevated levels of plasma triglycerides, leptin, FGF-21, PAI-1, and CCL11. GREKO mice featured constitutively enhanced levels of cutaneous GCs relative to controls at least partially due to keratinocyte-specific increased expression of the critical steroidogenic enzyme Cyp11b1. Also, the higher ratio of skin-secreted protective vs inflammatory adipokines in GREKO vs controls, correlated with higher capacity of adipogenic conversion in experiments using conditioned media from tissue explants. Following CORT treatment, relative to controls, GREKO mice featured reduced dWAT hyperplasia and adipocyte hypertrophy, with increased Adipoq and decreased Lipocalin 2 expression in purified dermal adipocytes. Conclusions: Overall data suggest that epidermal GR loss results in paracrine actions on dermal adipocytes as well as endocrine actions on key metabolic tissues that significantly improve the whole body metabolism in a mouse model of metabolic dysfunction.